Total antioxidant activity and trace elements in human milk: the first 4 months of breast-feeding - Matos, Carla (2009)
The content of many nutrients in breast milk are dependent on the nutritional status of the lactating woman. This is particularly true for fat and water-soluble vitamins, some of which have antioxidant properties. The aim of the study entertained herein was to evaluate the changes in total antioxidant status of human milk during the first 4 months of lactation, and to correlate such changes with the contents in specific antioxidant oligoelements (Cu, Zn, Mn and Se). Milk samples were collected from (31) lactating women recruited at the Service of Obstetrics of the Hospital de São João in Porto, after 1, 4, 8, 12 and 16 weeks after birth. The total antioxidant status (TAS) of human milk was measured by the Randox® commercial kit and trace metals by ICP-MS (inductively coupled plasma-mass spectrometry). The results found for TAS and oligoelements under study show a decrease in the concentration of these parameters from 7 days to 4 months of breast-feeding and significant correlations (p < 0.05) were found between TAS and Cu, Zn and Se (not Mn). The decreases of Cu, Zn and Se were also correlated, but not proportional between them, suggesting diverse excretion mechanisms for all. Between primipara and multipara women, a significant difference was found only for Cu and Zn concentrations at 7 days of lactation, but not for the other metals or TAS. With respect to the mother’s age, no correlation was found, either for trace metal concentrations or TAS.